Peacekeeping in Africa: Capabilities and Culpabilities - Ananda Nel (Scientia Militaria, 2012)
African states increasingly carry the responsibility for the promotion and maintenance of peace and security on the African continent. This book provides a detailed discussion on the efforts made by African states to do so and explores the ways and means to enhance Africa's peacekeeping capacity. An analysis is also made of external efforts to develop and enhance the capacity of African states to undertake peacekeeping operations. The content of this book is based on a two year research project conducted by means of fieldwork in more than 20 countries and interviews with more than 200 policy makers and members of civil society.